Study on different groups' perceptual image in religious tourism place based on place theory - Gao, Yan; Zhao, Zhenbin (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2016)
Based on the case of Lamgmu town, this research takes local Tibetan residents, Hui residents, tourists and merchants as respondents, and finds significant differences in spatial structure of perceptual image through the photo guiding semi-structured interview method. Using the social network analysis software UCINET combined with co-occurrence and social network analysis method, we build the four groups' spatial structure. Results have shown that the four groups form a series of same image hotspots and the same image hotspot hosts a diverse range of local perceptions; Under the influence of four groups' own cultural background and cognitive, the respondents show the different perceptions on the same place and form four types of image structures; The contact of co-occurrence between different places is mainly reflected in the following respects:the same geographical boundaries, nature complement, nature opposition; Additionally, local residents and migrant population show certain differences in cultural identi